2016
DOI: 10.1063/1.4967958
|View full text |Cite
|
Sign up to set email alerts
|

Non-equilibrium dynamics from RPMD and CMD

Abstract: We investigate the calculation of approximate non-equilibrium quantum time correlation functions (TCFs) using two popular path-integral-based molecular dynamics methods, ring-polymer molecular dynamics (RPMD) and centroid molecular dynamics (CMD). It is shown that for the cases of a sudden vertical excitation and an initial momentum impulse, both RPMD and CMD yield non-equilibrium TCFs for linear operators that are exact for high temperatures, in the t = 0 limit, and for harmonic potentials; the subset of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 98 publications
1
72
0
Order By: Relevance
“…In recent years, different efforts have been made to extend RPMD to describe nonadiabatic dynamics [86][87][88][89] and non-equilibrium conditions. 90 Very recently, Althorpe and co-workers have shown that RPMD can be viewed as an approximation to a more general type of quantum Boltzmann preserving classical dynamics, known as Matsubara dynamics. 42,43 However, so far, the formulation of RPMD has been restricted to the evaluation of the single-time Kubo transform.…”
Section: Rpmd Approximation Of the Symmetrized Double Kubo Transformmentioning
confidence: 99%
“…In recent years, different efforts have been made to extend RPMD to describe nonadiabatic dynamics [86][87][88][89] and non-equilibrium conditions. 90 Very recently, Althorpe and co-workers have shown that RPMD can be viewed as an approximation to a more general type of quantum Boltzmann preserving classical dynamics, known as Matsubara dynamics. 42,43 However, so far, the formulation of RPMD has been restricted to the evaluation of the single-time Kubo transform.…”
Section: Rpmd Approximation Of the Symmetrized Double Kubo Transformmentioning
confidence: 99%
“…Small differences in the dynamics resulting from the approximations in the sampling manifest themselves more strongly for short IR pulses than long IR pulses, due to less averaging in the former case. These shortcomings could, for example, be overcome by employing the ring polymer molecular dynamics approach [55,56] with nonequilibrium initial conditions [57] and surface hopping [58,59]. This is left for future work.…”
Section: +mentioning
confidence: 99%
“…There may also be other classical-like approximations to quantum dynamics (and maybe Matsubara dynamics) that for some systems are more accurate [145]. Very recent research has obtained out-of-equilibrium RPMD and CMD from Matsubara dynamics [20], which should be useful tools for excited state quantum dynamics.…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…We touch upon extensions to non-adiabatic dynamics towards the end. We generally assume that the systems being described are in thermal equilibrium; application to non-equilibrium systems is an interesting area of present research [20].…”
Section: Introductionmentioning
confidence: 99%